Anxiety of separation, is it from the child or from the parents? (Journal of Parents and Teachers, 2014)
On the first day of school takes place, on many occasions, the first long-term separation of the child and the parents. Before this event, it is normal that there is an anxiety and overwhelm of both the parents and the child. For this reason, this article offers some guidelines for educating competent children who can stand on their own and who do not fear separation.
Keywords: First day of school; separation; anxiety; overwhelm; fear; educational guidelines.